Infections in gynecology and obstetrics. Post-abortion infections. - Gutiérrez Aparicio, Carlos (2015)
In relation to septic abortion some observations concerning epidemiology, conditioning agents, bases and procedures for diagnosis and therapy, and preventive measures are carried out. A study of 57 cases of patients who presented with septic abortion pelviperitonitis and / or septic shock diagnosed and treated in a similar way also presented. It insists on the need to maintain based on the pathophysiology of the infection criteria, advocating that early diagnosis and rapid eradication of the septic focus by surgery are useful in reducing mortality.